사이코드라마에서 주인공이 경험한 소리 연구 - 김주현; Ju Hyun Kim (한국사이코드라마학회지, 2024)
본 연구의 목적은 사이코드라마에서 주인공이 경험한 소리를 탐색적으로 연구하여 개념도로 제시하는 데 있다. 이를 위하여 사이코드라마에서 소리가 풍부했던 회기 경험을 한 8명의 주인공을 목적 표집하여 심층 면담하였다. 최종 88개의 진술문을 추출하고 다차원 척도와 위계적 군집분석을 실시하였다. 도출된 개념도는 2차원 8개 범주이다. 차원의 축은 좌우 ‘외현적’과 ‘내현적’, 상하 ‘소리체현’과 ‘소리의 역할’이다. 8개 범주는 ‘정서 몰입 촉진’, ‘청각적 자극과 내면의 반향’, ‘비공명된 소리’, ‘울림의 정서 증폭’, ‘잉여현실의 정서 발현’, ‘정서적 에너지의 해방’, ‘소리와 몸의 정서적 연결’, ‘막힘과 발산의 혼재’로 나타났다. 본 연구는 사이코드라마에서 주인공이 경험한 소리에 대한 경험적 연구라는데 그 의의가 있다. The purpose of this study is to exploratively investigate the sounds experienced by protagonists in psychodrama and present them in the form of a concept mapping. For this purpose, eight protagonists who had experienced sessions with rich auditory elements in psychodrama were purposively sampled and interviewed in-depth. A total of 88 statements were extracted, and multidimensional scaling along with hierarchical cluster analysis was conducted. The resulting conceptual map consists of two dimensions and eight categories. The axes of the dimensions are: horizontal, from “explicit” to “implicit,” and vertical, from “sound embodiment” to “roles of sound.” The eight categories identified are: “promotion of emotional immersion,” “auditory stimuli and inner resonance,” “unresonated sound,” “amplification of emotional resonance,” “emotional expression in surplus reality,” “release of emotional energy,” “emotional connection of sound and body,” and “interplay of blockage and dispersion.” This study holds significance as an empirical investigation into the sounds experienced by protagonists in psychodrama.